Bulgaria’s European integration: prospects and unresolved issues regarding the country’s entry into the Eurozone - Vasil Petkov (Clío)
The relevance of the study is due to the fact that, despite Bulgaria’s achievement of the inflation criterion for joining the euro area, chronic political instability and social polarization continue to impede its full integration into the European monetary union. The purpose of the study is to examine the current situation in the direction of Bulgaria’s readiness to join the euro area by analysing trends and specifics of the main segments of the state’s domestic policy. The main methods are statistical, with the help of which the key indicators of the dynamics of economic formation and development of the country are considered, and the method of analysing regulatory documents, using which the legal acts in the field of European integration and development are analysed. A key aspect of European community development is addressing critical issues and responding to historical challenges. The gradual deepening of integration by intensifying cooperation in all areas and sectors determines the logical continuation of the rapprochement of the European Union states – the beginning of a single monetary system. The euro, as a common unit of payment, has substantially improved the quality and efficiency of financial and economic relations in the Union, but to join the euro area, it is necessary to meet certain criteria defined by the Maastricht Treaty. The results and best practices of the presented study can be used to develop the basis for forming recommendations and proposals for joining European structures.